Marxism, religion and ideology : themes from David McLellan - Bates,david,Ed; Mackenzie, Iain,Ed; Sayers, Sean,Ed; McLellan, David (Routledge studies in social political thought, 2018)
As austerity measures are put into place the world over and global restructuring is acknowledged by all as an attempt to bolster the economic system that lead to the crash, there is a great need to come to grips with the economic, political and philosophical legacy of Marx. Of particular interest are Marx’s analyses of alienation and the cycles of boom and bust thought to be integral to the functioning of capitalism. Moreover, as the Cold War drifts into the history books, it is possible to reconsider the lasting impact of Marx’s analyses without the shadows cast by the Soviet version of communism. Equally, though, scholars are increasingly turning to Marx for insight into the rise of religion and the corresponding demise of political ideologies that seems to mark the contemporary age. Are we witnessing ‘the return of Marx’?